A Review of Evolution and Applications of Telemedicine in Healthcare: Review Article (Journal of Pharma Insights and Research, 2025)
Telemedicine has emerged as a transformative force in healthcare delivery, particularly accelerated by the COVID-19 pandemic. This modal shift in healthcare delivery has revolutionized patient care by enabling remote consultations, monitoring, and treatment through digital platforms. The integration of advanced telecommunication technologies facilitates healthcare services across geographical, social, and temporal barriers. Telemedicine applications span various specialties, including dermatology, psychiatry, radiology, and chronic disease management, offering solutions for both urban and rural healthcare disparities. The technology employs multiple modalities such as real-time video consultations, store-and-forward systems, remote patient monitoring, and mobile health applications. While telemedicine presents numerous advantages, including improved healthcare accessibility, reduced costs, and enhanced patient compliance, it also faces challenges such as technological limitations, regulatory frameworks, and privacy concerns. The implementation of telemedicine has demonstrated significant benefits in clinical outcomes, patient satisfaction, and healthcare resource utilization. Healthcare providers increasingly adopt hybrid models combining traditional and virtual care delivery methods. Current evidence suggests that telemedicine will continue to evolve, incorporating artificial intelligence, advanced sensors, and integrated health information systems. However, successful implementation requires addressing infrastructure needs, regulatory requirements, and healthcare provider training while ensuring equitable access across diverse patient populations